Gravity gradient model of the Antarctic region derived from airborne gravity and DEM - Zhimin Shi; Xinghui Liang; Jinzhao Liu; Zhourun Ye; Junjian Lang; Zhibo Zhou; Lintao Liu (Earth, Planets and Space)
Abstract In this paper, we augment airborne gravity anomaly data from Antarctica, expanding the coverage area by 10.4% based on the existing data set. These data are combined with a gravity field model to establish a more comprehensive gravity anomaly database for Antarctica. Utilizing the Integral of Stokes Kernels' Derivatives (ISKD) method, we create the first 10 km resolution gravity gradient map in the Antarctic region. According to measured data in the McFaulds Lake (located in the James Bay lowlands of northern Ontario, Canada), the proposed method achieves a calculation accuracy with a standard deviation (Std.) of 3–7 E ( $$1 \text{E}=1× {10}^{-9}{s}^{-2}$$ 1 E = 1 × 10 - 9 s - 2 ) in $$Txx$$ Txx , $$Tyy$$ Tyy , $$Txy$$ Txy , $$Txz$$ Txz , $$Tyz$$ Tyz , and 12.9 E in $$Tzz$$ Tzz . The calculated gravity gradient effectively reveals density boundaries in Antarctica. This research lays the groundwork for future studies exploring the gravitational characteristics of Antarctica on a broader scale. Graphical Abstract